Periodic Solutions of Fractional Differential Equations with Delay - Lizama-Yanez, C (2011)
In this paper, we give a necessary and sufficient conditions for the existence and uniqueness of periodic solutions of inhomogeneous abstract fractional differential equations with delay. The conditions are obtained in terms of R-boundedness of operator-valued Fourier multipliers determined by the abstract model. © 2010 Springer Basel AG.